High power laser production of short-lived isotopes for positron emission tomography - Ledingham, K; McKenna, P; McCanny, T; Shimizu, S; Yang, J; Robson, L; Zweit, J; Gillies, J; Bailey, J; Chimon, G; Clarke, R; Neely, D; et al. (2004)
Positron emission tomography (PET) is a powerful diagnostic/imaging technique requiring the production of the short-lived positron emitting isotopes 11C, 13N, 15O and 18F by proton irradiation of natural/enriched targets using cyclotrons. The development of PET has been hampered due to the size and shielding requirements of nuclear installations. Recent results show that when an intense laser beam interacts with solid targets, megaelectronvolt (MeV) protons capable of producing PET isotopes are generated. This report describes how to generate intense PET sources of 11C and 18F using a petawatt laser beam. The work describing the laser production of 18F through a (p,n) 18O reaction, and the subsequent synthesis of 2-[18F] is reported for the first time. The potential for developing compact laser technology for this purpose is discussed.